2019
DOI: 10.1159/000501927
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib in the Treatment of Chronic Myeloid Leukemia and Philadelphia Chromosome-Positive Acute Leukemia: Recommendations of a German Expert Consensus Panel with Focus on Cardiovascular Management

Abstract: Treatment of chronic myeloid leukemia (CML) and Philadelphia chromosome-positive acute leukemia (Ph+ ALL) has been revolutionized with the advent of tyrosine kinase inhibitors (TKIs). Most patients with CML achieve long-term survival similar to individuals without CML due to treatment with TKIs not only in frontline but also in further lines of therapy. The third-generation TKI ponatinib has demonstrated efficacy in patients with refractory CML and Ph+ ALL. Ponatinib is currently the most potent TKI in this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
1
30
0
2
Order By: Relevance
“…Several mechanisms have been hypothesized to explain the ponatinib-induced toxicity profile, i.e., the simultaneous inhibition of cardiovascular-related kinases [ 11 ], but further studies are needed to fully characterize the ponatinib signaling pathway. It is of interest to understand why the extent of the ponatinib-induced cardiotoxicity observed among the patients is uneven [ 12 ], and whether it is sex-related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been hypothesized to explain the ponatinib-induced toxicity profile, i.e., the simultaneous inhibition of cardiovascular-related kinases [ 11 ], but further studies are needed to fully characterize the ponatinib signaling pathway. It is of interest to understand why the extent of the ponatinib-induced cardiotoxicity observed among the patients is uneven [ 12 ], and whether it is sex-related.…”
Section: Introductionmentioning
confidence: 99%
“…The Notch1 signaling influences multiple cell processes including differentiation, proliferation, apoptosis, migration, and angiogenesis. Notch1 has been shown to have both tumor suppressive and tumorigenic functions in different contexts [ 12 ]. Interestingly, it has been recently shown that a selective blockade of Notch1 can prevent vascular toxicity induced by ponatinib in human aortic endothelial cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of TKIs in the 2000s radically changed the fate of CML, since imatinib (IM), before, and nilotinib (NIL), dasatinib (DAS) or bosutinib (BOS), after, showed to be able to prevent the disease blastic transformation and significantly prolong the survival [ 20 , 21 , 22 , 23 ]. Achieving such a goal in up to 90% of the patient population treated first line with TKIs could mean that cure of CML have been finally achieved, but this is not completely true.…”
mentioning
confidence: 99%
“…Recent recommendations from a German expert consensus panel on ponatinib proposed the following criteria supporting a ponatinib starting dose of 30 mg/day in CML patients: chronic phase, good response status, no mutations, resistance to only one TKI, intolerance despite good response, and increased cardiovascular risk ( 35 ). The strategy to start ponatinib at doses lower than 45 mg/day should be guided by a thorough evaluation of risk factors, as well as the depth and stability of molecular response, and total exposure to ponatinib; continued monitoring of response is highly recommended ( 26 ).…”
Section: Suggested Strategies For Initiating Treatment With Ponatinibmentioning
confidence: 99%